Liss 2012 2013
DOI: 10.1007/978-3-642-32054-5_83
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Tourist Satisfaction of Tourism Destinations

Abstract: The present paper is a detailed sort-out and critical review of the foreign literature on tourist satisfaction at destinations in the last decade. Four dimensions that the relevant research surrounded are identified: tourist satisfaction theoretical model; the relation between tourist satisfaction and loyalty, expectation and service quality; the tourists' cultural backgrounds and cultural differences of the tourist satisfaction; and evaluation model of tourist satisfaction at destinations. The limitations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 52 publications
(68 reference statements)
0
13
0
2
Order By: Relevance
“…Chen, Zhang, & Qiu (2013) pointed that the destination image is not only an important factor to the tourists' travel decision and plans, but also to the tourist satisfaction. In the English Historic Towns Forum (1992), it was found that more than 80% of visitors considered the retailing mix and general environment of the town as the most important attraction of the destination.…”
Section: Destination Image In Relation To Tourist Satisfactionmentioning
confidence: 99%
“…Chen, Zhang, & Qiu (2013) pointed that the destination image is not only an important factor to the tourists' travel decision and plans, but also to the tourist satisfaction. In the English Historic Towns Forum (1992), it was found that more than 80% of visitors considered the retailing mix and general environment of the town as the most important attraction of the destination.…”
Section: Destination Image In Relation To Tourist Satisfactionmentioning
confidence: 99%
“…By the time the tourist arrives and starts enjoying the activities, perceptions concerning accessibility to tourist attractions may already have been formed. Not only does the anticipation stage help tourists to prepare their trips, but the resulting perception, whether positive or negative, may be a result of a comparison between what was anticipated and what was actually experienced, (Chen, Zhang, & Qiu, 2013;Pizam, Neumann, & Reichel, 1978). The preparatory set, then, deals with pre-information and anticipation, which may guide spatial behaviour to visit particular attractions.…”
Section: Preparatory Information Setmentioning
confidence: 97%
“…On the other hand, the conative image outlines the consumer's future desire or intention [77]. In the rural tourism context, tourists' visitation and expenditure originate from the concept of consumer behavior [78], and hence, brand image or destination image plays a crucial part in shaping the tourists' choice in making travel decisions [79]. Therefore, this study adopts destination appeals and tourism infrastructure as a tangible product or hard services as both constructs provide physical satisfaction to visitors.…”
Section: Hard and Soft Components Of Rural Tourismmentioning
confidence: 99%